Brucellosis in India: results of a collaborative workshop to define One Health priorities - Lindahl, Johanna F.; Vrentas, C.E.; Deka, Ram Pratim; Hazarika, R.A.; Rahman, Habibur; Bambal, R.G.; Bedi, J.S.; Bhattacharya, C.; Chaudhuri, P.; Fairoze, N.M.; Gandhi, R.S.; Gill, J.P.S.; et al. (Springer, 2020)
Brucellosis is an important zoonosis worldwide. In livestock, it frequently causes chronic disease with reproductive failures that contribute to production losses, and in humans, it causes an often-chronic febrile illness that is frequently underdiagnosed in many low- and middle-income countries, including India. India has one of the largest ruminant populations in the world, and brucellosis is endemic in the country in both humans and animals. In November 2017, the International Livestock Research Institute invited experts from government, national research institutes, universities, and different international organizations to a one-day meeting to set priorities towards a “One Health” control strategy for brucellosis in India. Using a risk prioritization exercise followed by discussions, the meeting agreed on the following priorities: collaboration (transboundary and transdisciplinary); collection of more epidemiological evidence in humans, cattle, and in small ruminants (which have been neglected in past research); Economic impact studies, including cost effectiveness of control programmes; livestock vaccination, including national facilities for securing vaccines for the cattle population; management of infected animals (with the ban on bovine slaughter, alternatives such as sanctuaries must be explored); laboratory capacities and diagnostics (quality must be assured and better rapid tests developed); and increased awareness, making farmers, health workers, and the general public more aware of risks of brucellosis and zoonoses in general. Overall, the meeting participants agreed that brucellosis control will be challenging in India, but with collaboration to address the priority areas listed here, it could be possible.